2020
DOI: 10.1111/scs.12874
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ required end‐of‐life care competence in health centres inpatient ward – a qualitative descriptive study

Abstract: Background Studies of nurses’ required competence in EOL care in health centres are rare. It is important to produce information about experienced nurses’ perceptions of the competence they consider important in their practical work. Aim The aim of this study was to describe nurses’ required competence in EOL care in health centre inpatient wards as experienced by nurses. Method A descriptive qualitative study using four semi‐structured group interviews (20 nurses) and inductive descriptive content analysis. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…Paramedics also requested for more education in encountering, communication, supporting, and counseling in end-of-life care. Our results are in line with previous studies, which identified supporting the patient and her/his family and carers as a nursing competence required by the professionals working in the basic level of palliative care 2730,37 as well as in palliative paramedicine. 22 The importance of encountering is also highlighted by family members of end-of-life patient as they are shown to emphasize professionalism and compassion of the paramedics’.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Paramedics also requested for more education in encountering, communication, supporting, and counseling in end-of-life care. Our results are in line with previous studies, which identified supporting the patient and her/his family and carers as a nursing competence required by the professionals working in the basic level of palliative care 2730,37 as well as in palliative paramedicine. 22 The importance of encountering is also highlighted by family members of end-of-life patient as they are shown to emphasize professionalism and compassion of the paramedics’.…”
Section: Discussionsupporting
confidence: 93%
“…Symptom management and use of opioids have been identified as ethical challenges also in previous studies 36 and competence in managing the most common symptoms as one of the main nursing competences in basic palliative care. 2830…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations